2018
DOI: 10.22432/pjsr.2018.16.11
|View full text |Cite
|
Sign up to set email alerts
|

Samodzielne Proces usamodzielnienia w doświadczeniach biograficznych byłych wychowanek placówek resocjalizacyjnych

Abstract: Artykuł poświęcony jest procesowi usamodzielniania się kobiet, które w przeszłości przebywały w placówkach resocjalizacyjnych. Do zilustrowania poruszanej tematyki wykorzystane wywiady narracyjne (wraz z właściwa procedurą analityczną F. Schütze) przeprowadzone z kobietami, które w przeszłości przebywały w młodzieżowym ośrodku wychowawczym. W oparciu o analizę uzyskanego materiału dokonano rekonstrukcji sposobów realizacji różnych form wsparcia w ramach procedury usamodzielnienia byłych wychowanek, tak jak uja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…The negative impact of the death of a loved one on a child's social development has been confirmed in research (see Feigelman et al 2017;Jaros, 2022), but the analysis made in this article showed that for most of the women studied, in their lifelong biographical experiences, the loss of a loved one was experienced as the dominant cause of the development of antisocial behavior.…”
Section: Agnieszka Jarosmentioning
confidence: 57%
See 1 more Smart Citation
“…The negative impact of the death of a loved one on a child's social development has been confirmed in research (see Feigelman et al 2017;Jaros, 2022), but the analysis made in this article showed that for most of the women studied, in their lifelong biographical experiences, the loss of a loved one was experienced as the dominant cause of the development of antisocial behavior.…”
Section: Agnieszka Jarosmentioning
confidence: 57%
“…22, No. 62, 63-72 as an experience that the respondents themselves define negatively, and which can activate many other risk factors inherent in the family (Łoś, 2011) and adversely alter the course of the respondents' biographies (Jaros, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…np. Jaros, 2022), a także -w mniejszym stopniu -diagnoza działalności samych pedagogów (wychowawców) (np. Dobińska, 2020) to tematy stale poruszane na łamach literatury.…”
Section: Wprowadzenieunclassified
“…Co to znaczy nosić etykietę "obcego" w instytucji totalizującej? Nie od dziś wiadomo, że pobyt w placówkach resocjalizacyjnych niesie ze sobą nieodwracalny bagaż o stygmatyzującym charakterze (Ambrozik, 2013;Jaros, 2022). Ciekawą perspektywę tego problemu charakteryzuje nam Agnieszka Jaros (2022).…”
Section: Wprowadzenieunclassified
See 1 more Smart Citation